1989
DOI: 10.1039/c39890001633
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and X-ray structure of bis(trifluoromethyl)(N,N-diethyldithiocarbamato)-copper; a remarkably stable perfluoroalkylcopper(III) complex

Abstract: The reaction between trifluoromethylcadmium reagent and Br2Cu(edtc) (edtc = N,N-diethyldithiocarbamato) or Cdl+[(CF3)2Cu]-with [Et2NC(S)S]2 in DMF (dimethylformamide) at -30 "C yields the stable Culll perfluoroalkylcopper complex, (CF&CuSC(S)NEt2.Perfluoroalkylcopper reagents exhibit excellent thermal stability compared to their hydrocarbon analogues and have consequently received extensive utilization in preparative organic chemistry ,1,2 but their composition and structure is not clearly defined. Perfluoro-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(107 citation statements)
references
References 0 publications
1
98
0
8
Order By: Relevance
“…It appeared that, whereas the reaction was successful, the Cu(III) species formed with R = alkyl rapidly decomposed into the stable copper(I) dithiocarbamate and other products from R. What I missed indeed was the use of a Cd(CF 3 ) 2 reagent and a fluorous alkyl group as shown by Willert-Porada et al in the late 1980s, because that would have resulted in the isolation of the stable diorganocopper(III) compound (CF 3 ) 2 CuS 2 CNEt 2 . 45 The second approach, based on the use of intramolecular coordination for the stabilization of the copper−carbon bond to form stable organocopper species, appeared in contrast to be extremely successful, however. 29a It resulted in the synthesis of stable organocopper(I) materials that, moreover, could be produced with acceptable purity and in larger quantities and hence facilitated our biological testing.…”
Section: ■ the Start Of My Journey In Organocopper Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…It appeared that, whereas the reaction was successful, the Cu(III) species formed with R = alkyl rapidly decomposed into the stable copper(I) dithiocarbamate and other products from R. What I missed indeed was the use of a Cd(CF 3 ) 2 reagent and a fluorous alkyl group as shown by Willert-Porada et al in the late 1980s, because that would have resulted in the isolation of the stable diorganocopper(III) compound (CF 3 ) 2 CuS 2 CNEt 2 . 45 The second approach, based on the use of intramolecular coordination for the stabilization of the copper−carbon bond to form stable organocopper species, appeared in contrast to be extremely successful, however. 29a It resulted in the synthesis of stable organocopper(I) materials that, moreover, could be produced with acceptable purity and in larger quantities and hence facilitated our biological testing.…”
Section: ■ the Start Of My Journey In Organocopper Chemistrymentioning
confidence: 99%
“…However, in 1989 (CF 3 ) 2 CuS 2 CNEt 2 was isolated and characterized (vide infra) as the first example of an organocopper(III) species. 45 Later homoleptic tetraorganocuprate(III) anions were reported: i.e., a [Cu(CF 3 ) 4 ]  anion with a bulky PNP cation. 83 In the meantime mechanistic studies of copper-catalyzed and -mediated reactions showed direct evidence that organocopper(III) intermediates were playing a crucial role in the product-forming step of many of these reactions.…”
Section: ■ Mononuclear Organocopper(ii) and Copper(iii) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Die Cu±C-und Cu±S-Absta È nde sind im Gegensatz zur homologen Trifluormethylkupfer-Verbindung (CF 3 ) 2 Cu(edtc) [7] symmetriebedingt jeweils gleich. Der ku È rzeste intra- [21].…”
unclassified
“…[124] Von Ullmann-Kreuzkupplungen von Arylhalogeniden wird gewçhnlich angenommen, dass sie über einen Cu I /Cu III -Katalysezyklus ablaufen (Schema 57), [120,125] [126] und auf der Grundlage von DFT-Rechnungen bestätigt. [127] [129][130][131][132][133] In den letzten Jahren wurden einige Kupfer(II)-und Kupfer(III)-Komplexe synthetisiert und kristallographisch charakterisiert, [134][135][136][137][138][139][140] und die erhaltenen Ergebnisse dienen als wichtige Grundlage bei der Betrachtung derartiger Intermediate in Cu-katalysierten Oxidationen. Mehrere dieser Komplexe wurden über Cu II -vermittelte Aktivierung einer C-H-Bindung eines Makrocyclus hergestellt.…”
Section: Hochvalente Organokupfer-komplexe In Nicht-oxidativen Reaktiunclassified